COAST Development Group's international consensus guidelines for the treatment of canine osteoarthritis - Cachon, Thibaut; Frykman, Ole; Innes, John F.; Lascelles, B. Duncan X.; Okumura, Masahiro; Sousa, Pedro; Staffieri, Francesco; Steagall, Paulo V.; Van Ryssen, Bernadette (Frontiers in Veterinary Science, 2023)
This report describes consensus guidelines and recommendations for the treatment of canine osteoarthritis (OA) according to the ‘Canine OsteoArthritis Staging Tool excluding radiography’ (COASTeR) stage of OA, by the COAST Development Group. The recommendations are based upon evidence-based medicine and clinical experience and are proposed with international relevance in mind. The aim is to provide veterinarians with a practical reference to consolidated information, to support the development of patient-specific OA management protocols and informed treatment choice based on the stage of OA. DISCLAIMER: Although every effort has been made to ensure the completeness and accuracy of the information provided herein, neither the authors nor Elanco Animal Health assumes any responsibility for the completeness or accuracy of the information. All information is provided "as is" without any warranties, either expressed or implied.